Effect of Dietary Supplementation of Aloe Vera and Amla Fruit Powder on Carcass Traits and Intestinal Microflora in Broiler Chickens - Gujar, Naushali; Arora, Rajni (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Effect of dietary supplementation with Aloe vera (Aloe barbadensis) and Amla fruit (Emblica officinalis) powder supplementation on carcass traits and intestinal microflora composition was evaluated in broiler chickens. The feeding trial was conducted under standard  feeding and managemental conditions with broiler starter (1-21 days) and finisher (22-35 days) ration on 240, day-old Vencobb broiler  chicks which were randomly divided into 4 treatment groups (T1 to T4) with four replicates of 15 chicks each. Birds were offered basal  feed as per the BIS. The treatment groups consisted of control group (T1) fed only with non-supplemented basal diet, group, T2 was  supplemented with 1% Aloe vera (Aloe barbadensis) powder, group T3 with 1% Amla fruit (Emblica officinalis) powder and group T4 with  0.5% Aloe vera (Aloe barbadensis) powder + 0.5% Amla fruit (Emblica officinalis) powder in basal feed. The supplementation of Aloe vera  (Aloe barbadensis) and Amla fruit (Emblica officinalis) powder alone and in combination showed highly significant (p
Keywords: Amla fruit powder, Aloe vera, Broiler, Carcass, Gut microflora